Hourly valve opening data of oysters Crassostrea gigas measured during a one-year semi-controlled experiment - Tran, Damien; Botté, Audrey; Geerebaert, Yannick; Payton, Laura (In: Tran, D et al. (2025): Valve behavior of the oysters Crassostrea gigas and Ostrea edulis and physicochemical data measured during a one-year semi-controlled experiment testing the in situ impact of artificial light at night [dataset bundled publication]. PANGAEA, https://doi.org/10.1594/PANGAEA.983250, 2025)
This dataset shows the hourly valve behavioral data of the 32 oysters Crassostrea gigas throughout the year of the experiment as well as the temperature recorded by each HFNI valvometer. The oyster valve behavior is characterized by 3 parameters: the Valve Opening Amplitude (VOA, the percentage of the valve opening relative to maximum opening), the Valve Opening Duration (VOD, the percentage of time that an oyster spends with its valves open), and the VOA/VOD. For each parameter, the data are presented for each oyster and as a group average for each condition. Missing data correspond to the death of oysters or the stopping of recording by a HFNI valvometer.
Keywords: Arcachon Bay; Artificial Light at Night; Crassostrea gigas; Field experiment; Ostrea edulis; Oyster; physiochemical parameters; valve behavior